Differential activity of the antioxidant defence system and alterations in the accumulation of osmolyte and reactive oxygen species under drought stress and recovery in rice (Oryza sativa L.) tillering - Xinpeng Wang (Nature Portfolio, 2019)
Abstract The objective of this study was to investigate the effects of drought stress on the activity of antioxidant enzymes and osmotic adjustment substance content in the tillering period of drought-sensitive and drought-tolerant rice cultivars. The results showed that the superoxide dismutase (SOD), peroxidase (POD), catalase activity (CAT), hydrogen peroxide content, soluble protein content and soluble sugar content increased with the accumulation of time and intensity of drought stress. Compared with the drought-sensitive cultivar, drought-resistant cultivar had a smaller photosynthetic affected area, longer CAT enzyme activity duration, and lower H2O2 accumulation. Unlike POD and CAT enzymes, which maintain the ability to scavenge hydrogen peroxide under long drought conditions, ascorbate peroxidase (APX) enzymes seem to be a rapid response mechanism to scavenge hydrogen peroxide under drought stress. Under a −10 kPa water potential, using soluble sugars on the osmotic adjustment ability of the drought-resistant cultivars was more efficient; under −40 kPa water potential, drought-resistant cultivars can maintain relative high levels of ascorbate (ASA) content in the short term. After the restoration of irrigation, the indices gradually returned to control levels. The ASA content showed faster accumulation ability in drought-resistant cultivars and faster recovery. The soluble protein content recovered more slowly in drought-sensitive cultivars under the −40 kPa treatment. Drought-resistant cultivars showed stronger resistance to drought in the −10 kPa treatment and obtained similar yield to the control, while the drought-sensitive cultivars were more obviously affected by the drought stress.